5PSQ-003 performance of a cold maintenance device during the implementation of a pneumatic circuit. Issue 1 (23rd March 2023) - Ferrari, C; Modeste, H; Besnier, P; Baveux, R; Collet, CE; Saint-Lorant, G
Abstract : Background and Importance: Few information are available about the performance of cold maintenance device. Within the framework of the implementation of a pneumatic system in a new university hospital, the feasibility of sending different types of medicines, including cold products with a pneumatic system was studied. Aim and Objectives: The objective of this study is to evaluate the compliance of a cold maintenance device within a pneumatic. Material and Methods: The study was led in a French University Hospital with 1495 beds and more than 80 care units between May and September 2022. The analysis was made with kits provided for the cartridges dedicated to cold transport and with qualified electronic temperature recorders Log-tags ® (C.M.I France, Neung-sur-Beuvon). Different conditions were tested, one condition per test, reproduced at least 3 times: kits placed at room temperature, in the fridge (2/8°C) or in the freezer, presence or not of a secondary packaging, eutectic plate or putting the kit in the cartridge. The supplier had certified on his commercial leaflet a duration of 50 min between 2 and 8°C under the following conditions: 500 ml infusion bag stored at 5°C, with thermal recorder inside the bag, placed in the kit then in the cartridge. Results: All the results of the 9 different tests (one condition per test, reproduced at least 3 times) do not meet the 50 min data indicated by the supplier. The method applied by the supplier shows a mean duration between 2 and 8°C of 4.20 min [4;5] Using the same starting conditions: freezing the kit, gave an average of 8.20 min [7;9], using a secondary packaging, the average was 6.40 min [6;7], outside the cartridge, the average was 4.40 min [4;6], and adding an eutectic plate, the average was 29.24 min [11;60] but with a temperature below 0°C. The average for all tests is 8.46 min. Conclusion and Relevance: This study showed that the supplier's device and data did not comply the good practices concerning management of health products subject to cold chain and the patient safety. Various studies have been undertaken at the level of the Hospital pharmacy and the cold supplier to improve the supplied isothermal enclosure. References and/or Acknowledgements: Conflict of Interest: No conflict of interest